(untitled) (LEARNing Landscapes, 2016)
In the last few years, the use of creative assessments has been shown to be e ective in addressing students’ di erent learning styles and nurturing their personal and academic growth. This article presents the framework for the activities and assessments of the Art & Science Project,1 which is designed to engage learners by using visual arts to portray scienti c concepts. The project’s goal is to promote cross-disciplinary integration and a deeper understanding of the crucial role of models in science. The history of the project and the technologies used to support a creative environment are described.